Idea to image in Photoshop CS2 : Rick Sammon's guide to enhancing your digital photographs - Sammon, Rick (Peachpit Press, 2006)
Learn how to take digital photographs and work with Photoshop to turn normal digital images into creative and imaginative ones. Techniques such as aging an image, creating a montage, enhancing an action shot, and hand-coloring a photograph are included.